PENGARUH HARGA, PELAYANAN DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA PANGKAS RAMBUT BANG ARDHI DI SITUBONDO - Nugraha, Ragil Putra (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This research was conducted with the aim of knowing the impact of partially, simultaneously and dominantly variables of Price, Service and Location on the variable of consumer satisfaction at Bang Ardhi Barbershop in Situbondo. The research method uses observation, literature study, and documentation.The result of this reseach is multiple linier regression equation Y = 1.453E-16 – 0,004 X1 + 0,282 X2 + 0,351 X3 + e.. Value of tcount for the variable Price is -0.037. While the value of the 5% distribution ttable is 1.986, then tcount -0.037 > ttable -1.986 means Ho is accepted or Ha is rejected. The value of tcount for the Service variable is 2.750. While the value in the 5% distribution ttable is 1.986, then tcount 2.750 > ttable 1.986 means Ho is rejected or Ha is accepted. The tcount for the Location variable is 3.747. While the value of the 5% distribution ttable is 1.986, then tcount 3.747 > ttable 1.986 means Ho is rejected or Ha is accepted. Comparing the value of Fcount > Ftable, 8.508 > 2.71, based on statistical testing using the F-test method, where the significant level obtained is 0.000 < 0.05. The dominant test of research is the variable X3 Location of 3.747 which is greater than the value of the variabel X1 Price of -0.037 and the variabels X2 Service of 2,750.